Study of the Stability in the High Building: Case Study in Burj Dubai, UAE - Mohammed Ahmed Omar Bakarman; Muhammad Ikhsan Setiawan; Adi Prawito (Neutron, 2023)
Many people today live in urban cities and it is increasing every year, because of their need to live and work and This paper summarizes the solutions and the importance of stability in high-rise buildings and their tolerance of earthquakes and winds, and all that is needed for the stability of the building and to solve the problems that occur in particular and in detail Highlighted are the key connections of the tallest and ultra-slender buildings that have been designed and built for the world's tallest buildings. He talks about high-rise towers in general and about Burj Dubai in particular, and there will be what the engineers said and suggested before, and I will conclude in a simple way.